Niger : Assessment Letter for the African Development Bank. (Policy Papers; Policy Paper ;, 2012)
The new three-year ECF arrangement was approved by the Board on March 16, 2012. The economic outlook for 2012 and 2013 is broadly positive, thanks to the coming onstream of oil production and continuing investment in the natural resource sector. Downside risks to the outlook include the fragile regional security situation and climatic shocks. Program implementation in 2012 has been mixed. All end-June quantitative performance criteria were met other than the continuous performance criterion on non-concessional borrowing, but there were delays in the execution of the structural reform agenda.